Morphological identification of anaplasmataceae-like organisms in monocytes of the hybrid surubim catfish (pseudoplatystoma reticulatum x p. corruscans) - Case report - Ishikawa, Márcia Mayumi (2011)
The aim of this study was to report the occurrence of Anaplasmataceae-like organisms in monocytes from the hybrid surubim catfish. During the hematological evaluation of fish infected by Pseudomonas sp. in a fish farm located in the State of Mato Grosso do Sul we observed into the monocytes the presence of numerous pleomorphic inclusions of various sizes, rough in appearance which presented basophilic staining. These inclusions were similar to elementary bodies, initial bodies and morule of the bacteria from Anaplasmataceae family, often diagnosed in domestic mammals. This is the first report of its occurrence possibly belonging to the family of Anaplasmataceae in cultured fish in Brazil. Additional studies are necessary for molecular characterization of this bacteria, pathogenic potential, life cycle and impact on the intensive production of fish.